지역별 오미자의 리그난 함량 및 분석법 검증 - 황병순(Byung Soon Hwang); 김기창(Gi-Chang Kim); 박영희(Young Hee Park); 황인국(In Guk Hwang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
본 연구는 재배지역별 오미자의 리그난 함량을 조사하기 위해 수행되었다. HPLC를 사용하여 특이성, 직선성, 검출한계(LOD), 정량한계(LOQ) 및 정확도를 결정함으로써 리그난의 분석법이 검증되었다. 리그난 중에는 schizandrin이 3.85~6.60 mg/g으로 가장 풍부했고 그다음 gomisin N이 2.69~4.38 mg/g으로 많았다. Schizandrin A와 gomisin A는 0.60~2.04, 0.86~1.63 mg/g이었고, gomisin G, gomisin H, gomisin J는 0.5 mg/g 미만이었다. 오미자의 리그난 화합물 7종 함량은 9.04~14.90 mg/g이었다. 재배지역별 오미자는 각 리그난의 함량은 다르지만 전체 함량에는 큰 차이가 없다. 오미자 표준화를 위한 기초자료로 유용할 것으로 기대된다. This study examined the lignans (schizandrin, schizandrin A, gomisin A, gomisin G, gomisin H, gomisin J, and gomisin N) contents in the fruit of Omija (Schisandra chinensis) according to the cultivation region. The methods for determining lignans were validated by measuring the specificity, linearity, limit of detection (LOD), limit of quantification (LOQ), precision, and accuracy using HPLC analysis. Among the lignans, schizandrin was the most abundant (3.85∼6.60 mg/g) followed by gomisin N (2.69∼4.38 mg/g). Schizandrin A and gomisin A were approximately 0.60∼2.04 and 0.86∼1.63 mg/g, respectively, and gomisin G, gomisin H, and gomisin J were less than 0.50 mg/g. The contents of seven lignans of Omija were 9.04∼14.90 mg/g. Omija showed different contents of lignans according to the cultivation region, but there was no significant difference in the total contents. These results will provide valuable basic data for the standardization of Korean Omija. KCI Citation Count: 4